2014
DOI: 10.5194/amtd-7-3591-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A wide field-of-view imaging DOAS instrument for continuous trace gas mapping from aircraft

Abstract: Abstract. For the purpose of trace gas measurements and pollution mapping, the Airborne imaging DOAS instrument for Measurements of Atmospheric Pollution (AirMAP) has been developed, characterised and successfully operated from aircraft. From the observations with the AirMAP instrument nitrogen dioxide (NO2) columns were retrieved. A major benefit of the pushbroom imaging instrument is the spatially continuous, gap-free measurement sequence independent of flight altitude, a valuable characteristic for mapping … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Therefore, the VCD (Eq. 7) may be defined as the ratio of the SCD to the AMF (Solomon et al, 1987) VCD = SCD AMF .…”
Section: Air Mass Factor Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the VCD (Eq. 7) may be defined as the ratio of the SCD to the AMF (Solomon et al, 1987) VCD = SCD AMF .…”
Section: Air Mass Factor Computationmentioning
confidence: 99%
“…how this change might impact the AOD and in turn the AMF, the OPAC aerosol model (Hess et al, 1998) was used to estimate the impact with a continental average aerosol configuration. The results showed that an increase in RH from 50 % to 60 % would lead to an 8 % increase in AOD at 450 nm.…”
Section: Regional Summarymentioning
confidence: 99%
“…CHOCHO, from space (e.g., Burrows et al, 1999;Martin et al, 2002;Richter et al, 2005;Wittrock et al, 2006;Schön-hardt et al, 2008;De Smedt et al, 2008) as well as from the ground, ships and aircafts (e.g., Wittrock et al, 2004;Heckel et al, 2005;Peters et al, 2012;Pinardi et al, 2013;Groß-mann et al, 2013;Schönhardt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These data can be used for top-down estimates of atmospheric surface fluxes of local sources via inverse modeling (Krings et al, 2011(Krings et al, , 2013. In addition to the MAMAP instrument, also a push-broom imaging DOAS spectrometer instrument for remote sensing measurements of nitrogen dioxide (NO 2 ) was installed on the aircraft, as described in Schönhardt et al (2014).…”
Section: Remote Sensing Instrumentation For Atmospheric Greenhouse Gamentioning
confidence: 99%